WAVELENGTH OF THE He-Ne LASER BY USING TWO TYPES OF DIAPHRAGM DIFFRACTION METHODS - Purwaningsih, Sri; Falah, Hebat Shidow; Lestari, Neneng; Sitinjak, Hardiantinus; Mousa, Almahdi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
Light diffraction, characterized by the spreading or bending of waves when encountering narrow obstacles, forms the focal point of this research endeavor. Utilizing the circular diffraction method, this study pioneers the identification of the He-Ne laser wavelength through experimentation with both three and five-slit diaphragms. The investigation with a three-slit diaphragm involves three variations in slit distances: d = 0.125 mm, 0.25 mm, and 0.5 mm at a screen distance of 150 nm, revealing diffraction patterns across three orders of magnitude. For the five-slit diaphragm, the analysis extends to a slit distance of d = 0.25 nm and a layer distance of 320 nm. Interestingly, the results reveal that the wavelength spectrum of the He-Ne laser depends on the variation of the gap distance. Remarkably, a gap distance as minimal as 0.25 nm yields wavelengths within the range of 641 nm to 660.67 nm, highlighting the diffraction process's sensitivity to minute variations in experimental parameters. This groundbreaking research not only elucidates the intricate interplay between light diffraction and experimental configurations but also underscores the circular diffraction method's versatility in determining the fundamental properties of laser light. This study paves the way for advancements in optical instrumentation and characterization techniques by offering novel insights into wavelength determination methodologies. These findings have far-reaching implications across diverse scientific disciplines, including physics, materials science, and optical engineering, enhancing the precision and capability of optical measurement technologies.